Characterisation of aroma profile and evaluation of aroma quality in sweet cream butter. (March 2021) - Tamura, Hirotoshi; Ueno, Shoko; Naka, Azusa; Zhao, Huajie; Yonekura, Lina; Isogai, Tomoyuki; Wakui, Ryota; Shiota, Makoto
Abstract: The objective of this study was to determine which volatile compounds are responsible for the aroma of fresh sweet cream butter, using a liquid–liquid extraction method coupled with a Porapak Q column and limited odour units (Lod) as technical methods. Sixty-four compounds were quantitatively identified. Assessors determined 100 ppm as the critical concentration for good aroma. Individual Lod100 were calculated at 100 ppm of the extracted oil using each compound's thresholds and then twenty-three chemicals such as δ-dodecalactone, δ-decalactone, γ-decalactone, acetaldehyde, and decanoic acid were selected as the potent aroma compounds in terms of Lod100 values greater than one.